Caso de estudio: Análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Rodriguez Blanco, Jorge Armando (2019)
Current document is based on a strategic analysis of Camposol and the process it went through to become the largest agricultural producer and largest plantation of avocado in Peru as well as the world’s largest blueberry producer. This document will organize an internal diagnosis of the business model and supply chain where we will list the activities to generate end products such as fruits, vegetables and seafood, which then are packed and commercialized worldwide. This way we will manage to define the competitive advantage, which will support the company progress and UEN. We will also do an external company diagnosis with a PEST analysis where we will detail its current position in 4 blocks (legal-political, economic, socio-cultural and technological). At the same time, we will determine the competitive strength in the agrobusiness sector, as well as opportunities and challenges that Camposol represents. We will additionally use the definition of mission, vision and politics at the organizational level to understand Camposol objectives and projections. Also, to formulate correctly the strategy to follow, we will do an analysis of strengths, opportunities, weaknesses and threads, so that they can be inserted in EFI and EFE matrix and hence detect mitigation mechanisms for potential weaknesses and threads and maximize opportunities and strengths. Finally, we will organize an evaluation at the organizational structure level of Camposol to elaborate proposals to improve execution strategies to continue companies’ expansion and positioning in the fresh food market.